MODIFIKASI PATI SECARA ASETILASI DAN APLIKASINYA PADA PEMBENTUKAN FILM - Nurhayati Nurhayati (Universitas Muhammadiyah Mataram, 2019)
Along with the development of technology and processing methods used, native starch can be modified to improve its chemical, physicochemical characteristics so that it can be utilized for further products. Modified starches are starches whose hydroxyl groups have been changed by a chemical reaction (esterification, etherification, or oxidation) or by disturbing the original structure. One method of chemical starch modification commonly used is acetylation, which produces acetylated starch. Acetylated starches are produced from starch granules ethered with acetate groups by substituting starch hydroxyl groups. Chemical starch modification by acetylation with inserting an acetyl group in the OH group starch through the acetylation reaction. The reagents commonly used in the acetylation method are vinyl acetate, acetic acid, and acetic anhydrous. Acetylated starch has the physicochemical properties advantages such as gelatinization temperature, development power, solubility, and paste clarity are high. Another advantage is better storage and cooking stability when compared to native starch. In addition, the quality of the products produced from starch acetate is more stable and resistant to retrogradation. In general, starch modification by acetylation is greatly influenced by several factors, including intrinsic and extrinsic factors. Intrinsic factors include the structure of the granules (the shape and size of the granules), the composition of the granules (ratio of amylopectin and amylose, and compositions other than starch). While extrinsic factors consist of reagents (reagent type, concentration), condition of the media reaction (temperature, pH, reaction time, and pressure ), these factors will affect the degree of substitution,% acetyl, physicochemical, morphological and rheological properties, thermal and pasting of acetylated starch. In its application based on the degree of substitution, acetylated starch is classified into three levels, namely low, medium, high. Acetate starch with low DS (0.01-0.2) can function as film-forming, binder, adhesive, thickener, stabilizer, and texturing agent.